Creative Industries’ Perspectives on AI’s Potential Impact on Creative Jobs: Qualitative Study on Creative Professionals in Yogyakarta and Surrounding Areas - Pranandari, Rizka Putri; Aoyama, Atsushi (Asian Journal of Innovation and Entrepreneurship, 2026)
The widespread uses of AI in creative industries are unavoidable. Thus, the impacts of AI on human jobs in creative industries are very intriguing to be investigated. This study aims to explore the perspectives of creative professionals regarding to AI’s impacts on human jobs in their respective industries. The qualitative data collected from in-depth interviews on 10 creative professionals are analyzed using thematic analysis approach. Our analysis resulted in eight main themes and 18 categories. There are four important findings to be highlighted from this study. First of all, the positive and negative impacts of AI depend on the quality of human resources. Secondly, the positive and negative impacts of AI also depend on individual’s wisdom and mindset. Third, in principle, AI is merely assistive tools for human and the uses of AI are optional and depending on human’s need. Finally, the diverse opinion about AI’s impact might be influenced by human’s role in the economic system.